An Analysis Of Students’ Ability In Writing Paragraph - Desi Andriani (Fakultas Sastra Universitas Ekasakti, 2025)
This article concerns about students’ ability in writing paragraph. A paragraph is the basic unit of writing that functions as a bridge between sentences and larger sections of text, usually expressing a single idea or topic. The population of the research was students of management of UPI YPTK Padang. Sample was students of second semester in 2024/2025 academic year. They were forty five students. The research used test as instrument. The data were taken by asking students to write paragraph. The result of the study showed that students had different ability in writing paragraph.